2022
DOI: 10.3390/nu14235014
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals: A Promising Therapeutic Approach in Ophthalmology

Abstract: Oxidative stress represents one of the main factors driving the pathophysiology of multiple ophthalmic conditions including presbyopia, cataracts, dry eye disease (DED), glaucoma, age-related macular degeneration (AMD) and diabetic retinopathy (DR). Currently, different studies have demonstrated the role of orally administered nutraceuticals in these diseases. For instance, they have demonstrated to improve lens accommodation in presbyopia, reduce protein aggregation in cataracts, ameliorate tear film stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 249 publications
0
14
0
Order By: Relevance
“…Investigating nutraceuticals as a preventive or complementary strategy for SANS management reflects a holistic approach to astronaut health. Nutraceuticals aim to address nutritional deficiencies and enhance ocular resilience, contributing to preventing and managing SANSrelated ocular changes [50].…”
Section: Potential Pharmacological Treatmentsmentioning
confidence: 99%
“…Investigating nutraceuticals as a preventive or complementary strategy for SANS management reflects a holistic approach to astronaut health. Nutraceuticals aim to address nutritional deficiencies and enhance ocular resilience, contributing to preventing and managing SANSrelated ocular changes [50].…”
Section: Potential Pharmacological Treatmentsmentioning
confidence: 99%
“…Stote, K.S. et al conducted a randomized, single-blind human intervention trial using 100% wild blueberry juice and observed that the short-term consumption of 240 mL of wild blueberry juice per day may promote cardioprotective effects in adults at risk of type 2 diabetes by improving the systolic blood pressure (possibly through nitric oxide production) [112,113]. The berries and stilbene in blueberries also exhibit preventive effects for several cancers [114].…”
Section: Health Value and Prospects Of Blueberriesmentioning
confidence: 99%
“…Despite obvious limitations, preclinical and clinical studies strongly support the role of nutraceuticals in the management of sight-threatening retinopathies [ 25 , 88 , 89 ], as thoroughly reviewed in other recent publications [ 87 , 90 , 91 ]. Differently, in the present review, we aim to provide a pragmatic overview of the intersection between the use of pharmaceutical drugs and food supplements intended as nutraceuticals.…”
Section: Nutraceuticals: Which Place In the Management Of Neovascular...mentioning
confidence: 99%